Parameter Al-Dharīah menurut perspektif Syariah (Parameter of Al-Dharīah from The Perspective of Shari’ah) - Mohd Aswadi, Mohamad Shafiq; Md. Sawari, Mohd. Fuad; Sitiris, Miszairi; Baharuddin, Ahmad Syukran (Intelligentia Resources, 2021)
Al-Dharīʿah is an important concept in the issuance / establishment of Islamic law. In general, it covers two main parts, namely sadd al-dharīʿah and fath al-dharīʿah. However, this second part (fath al-dharīʿah) is less discussed in depth and extensively by previous scholars. Thus, this study is to produce pragmatic and practical parameters of al-dharīʿah according to the perspective of Sharīʿah. This study uses a library research methodology. The results of this study show that the parameters of al-dharīʿah produced must be holistic and comprehensive to cover the scope of sadd and fath al-dharīʿah so that the law issued/inferred can lead to permissible laws (such as obligatory, preferable and allowable) or vice versa. The researcher suggested a solution so that the parameters of al-dharīʿah that have been produced can be applied in contemporary matters such as Islamic finance, halal industry, education, medicine and so on to ensure that Sharīʿah law is maintained and ensure that the Maqāṣid al-Sharīʿah is achieved perfectly.